Artifactual hypoglycemia caused by Raynaud’s phenomenon: A case report with literature review - Nishioka, Hidenori; Yamamotoya, Takeshi; Itoda, Yuki; Ichikawa, Chikako; Nishiyama, Mai; Takubo, Masahiro; Nagasawa, Akiko; Kosuda, Minami; Egashira, Fujiko; Fujishiro, Midori; Watanabe, Kentaro; Ishihara, Hisamitsu (Frontiers in Endocrinology, 2025)
Finger-stick glucose monitoring is commonly used in the clinical management of diabetes as a tool to obtain a reliable estimate of venous glucose levels. However, it should be noted that discrepancies can arise in certain situations between the finger-stick glucose value and venous blood glucose concentration. We present herein the case of a 76-year-old woman with dermatomyositis presenting with artifactual hypoglycemia, in which finger-stick glucose monitoring exhibited false-low values due to Raynaud’s phenomenon. Despite the low glucose level (<54 mg/dL) on finger-stick glucose monitoring, she was asymptomatic, and occasional laboratory blood tests failed to detect apparent hypoglycemia. We suspected artifactual hypoglycemia to be caused by Raynaud’s phenomenon, and consistently, switching the blood sampling site from the finger to the earlobe ameliorated the discrepancy against the actual venous glucose levels. Given the prevalence of steroid-induced diabetes in patients with Raynaud’s phenomenon, clinicians should be aware that finger-stick glucose monitoring can present false-low values due to Raynaud’s phenomenon, thus avoiding unnecessary investigations searching for the cause of “hypoglycemia,” or conversely, preventing underestimation of the actual hyperglycemia.